2015
DOI: 10.4172/1522-4821.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder after Hurricane Sandy among Persons Exposed to the 9/11 Disaster

Abstract: Background-Traumatic exposure during a hurricane is associated with adverse mental health conditions post-event. The World Trade Center Health Registry provided a sampling pool for a rapid survey of persons directly affected by Hurricane Sandy in the New York City (NYC) metropolitan area in late October 2012. This study evaluated the relationship between Sandy experiences and Sandy-related posttraumatic stress disorder (PTSD) among individuals previously exposed to the September 11, 2001 (9/11) disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 21 publications
(32 reference statements)
7
75
1
1
Order By: Relevance
“…It was the second costliest cyclone to hit the U.S. since 1900 (Blake et al, 2013). While several studies have examined the mental health impact of Sandy among exposed adults (Boscarino et al, 2014; Caramanica et al, 2015; Neria and Shultz, 2012), no studies have documented the impact of Sandy on pregnant mothers and their offspring over time.…”
Section: Introductionmentioning
confidence: 99%
“…It was the second costliest cyclone to hit the U.S. since 1900 (Blake et al, 2013). While several studies have examined the mental health impact of Sandy among exposed adults (Boscarino et al, 2014; Caramanica et al, 2015; Neria and Shultz, 2012), no studies have documented the impact of Sandy on pregnant mothers and their offspring over time.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the health impact of Sandy among those who lived in Sandy–flooded areas and elsewhere, a survey of 8,870 adult Registry enrollees who participated in Wave 3 survey was conducted between March 28 and November 7, 2013, 5 to 12 months after Sandy (Caramanica et al, 2015). Detailed descriptions of survey sampling and methods are described elsewhere [Brackbill et al, 2014].…”
Section: Methodsmentioning
confidence: 99%
“…Preexisting mental health disorders may also increase vulnerability to subsequent trauma (Breslau et al 2008; Caramanica et al, 2015; Bromet et al, 2017). A study of 9/11-exposed populations including WTC responders and non-responders found those with pre-Sandy 9/11-related PTSD symptoms were nearly 7 times more likely to report having Sandy-related PTSD symptoms 5–12 months post-Sandy than those without pre-Sandy PTSD symptoms (Caramanica et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations